Effect of endodontic treatment on clinical outcome in type 2 diabetic patients with apical periodontitis - Shengming Wang; Xiaoqing Wang; Feng Bai; Xinlian Shi; Tingting Zhou; Fangfang Li (Heliyon, 2023)
Background: Previous research has demonstrated that poor controlled diabetic showed higher prevalence of AP compared to well-controlled patients and endodontic treatment may improve metabolic control of patients with diabetes. The purpose of this trial was to clinically assess the effects of endodontic treatment on glycemic control in patients with type 2 diabetes mellitus (T2DM) and apical periodontitis (AP). Study design: For present trial, AP + T2DM with patients insulin injection (Group1, G1,n = 65), AP + T2DM patients with hypoglycaemic agents (Group2, G2, n = 82), and AP patients without DM (Group3, G3, n = 86) were enrolled. After demographic characteristics and clinical examination were achieved, root canal treatment (RCT) was performed for each patient. Subjects were followed up at 2-week, 3- and 6-month. At each visit, blood samples were taken and clinical laboratory studies were performed. At 6-month follow-up, Periapical Index (PAI) score was used to assess the periapical status. Results: A total of 237 subjects who met the including criteria were allocated in three groups and 223 subjects (94.1%) completed the treatments and the follow-up assessments. After treatment, taking PAI into consideration, both groups showed significant improvement of AP in each group (P < 0.05). Patients in G3 had a continued significant lower concentration of fasting plasma glucose (FPG) levels at follow-up (P < 0.05). A continued reduction of hemoglobin glycation (HbA1c) was observed in most of time points (P < 0.05). Throughout the trial, there are also significant changes in inflammatory factors in short-term. Conclusion: Endodontic therapy improved AP healing, glycemic control and systemic inflammation in patients with T2DM and/or AP in each group. However, a continued reduction in inflammatory factors and decreasing of HbA1c in short-term could not be observed in this trial.